Acute and subacute symptoms among workers in the printing industry. Issue 1 (February 1982) - Baelum, J; Andersen, I; Mølhave, L
Abstract : The study population comprised 52 male printers and 52 controls. Each person was interviewed about job history, general health, and work-related symptoms. Symptoms from eyes and airways, neurological symptoms, and general symptoms were recorded. A lung function test and a measurement of the sense of smell were also carried out. The printers had significantly more eye, airway, and neurological symptoms than the controls; the main complaints being irritation of eyes, nose, throat, and a reduced sense of taste. The neurological symptoms were disorders of vision, vertigo, feeling of intoxication, and headache. Furthermore, abdominal pain and flatulence occurred more often among the printers. The symptoms showed no relation to age or job seniority, but neurological and general symptoms were related to shift work. No difference in lung function was found between the two groups. The printers had a slightly lower threshold of smell than the controls. Although the total load due to organic solvents and dust in the air was far below legal limits, the number of magnitude of symptoms experienced by the printers exceeded what is supposed when norms for workroom exposure are set. It is suggested that either the irritative effects of solvents are underestimated or the assumption of additive effects when great numbers of solvents are found does not hold true. A reduction of the number of solvents by eliminating the most toxic solvents or by using dyes without solvents is suggested.